2012
DOI: 10.1073/pnas.1208341109
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of hydrogen atom dynamics and interactions by ultrahigh resolution neutron protein crystallography

Abstract: The 1.1 Å, ultrahigh resolution neutron structure of hydrogen/ deuterium (H/D) exchanged crambin is reported. Two hundred ninety-nine out of 315, or 94.9%, of the hydrogen atom positions in the protein have been experimentally derived and resolved through nuclear density maps. A number of unconventional interactions are clearly defined, including a potential O─H…π interaction between a water molecule and the aromatic ring of residue Y44, as well as a number of potential C─H…O hydrogen bonds. Hydrogen bonding n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 43 publications
(52 reference statements)
0
38
0
Order By: Relevance
“…Finally, a very recently determined ultra-high-resolution neutron structure of the protein crambin emphasizes that CH⅐⅐⅐O hydrogen bonds represent only one class of a large category of underappreciated interactions in biomolecules (69). In addition to many CH⅐⅐⅐O hydrogen bonds, the authors directly observed many acceptor hydrogen bonds.…”
Section: Discussionmentioning
confidence: 91%
“…Finally, a very recently determined ultra-high-resolution neutron structure of the protein crambin emphasizes that CH⅐⅐⅐O hydrogen bonds represent only one class of a large category of underappreciated interactions in biomolecules (69). In addition to many CH⅐⅐⅐O hydrogen bonds, the authors directly observed many acceptor hydrogen bonds.…”
Section: Discussionmentioning
confidence: 91%
“…46 Evidence for more (acidic) labile C-H groups has also come from H/D exchange patterns in the atomic resolution neutron structures of cobalamin and crambin. 14,15 The case of crambin is particularly interesting because it involves partial exchange of one of the H atoms bound to a C α (on Gly31), evidence of potential C-H. . .O H-bonding.…”
Section: Unusual Chemical Bonds Involving Hydrogenmentioning
confidence: 99%
“…They have been proposed [209] to act as the principal driving force for folding of β,γ-hybrid model peptide and of the structure of amicyanin [210]. Ultrahigh resolution neutron diffraction data of proteins [211] have noted CH··O HBs with an average HB length of 2.0 Å. These bonds are essential ingredients of oligosaccharides and carbohydrates where they have been estimated [198] to account for as much as 40 % of the total interaction energy.…”
Section: Other Systemsmentioning
confidence: 97%